Bahasa Inggris - Tisa Gianesa Suzry; Ahmad Fauzi; Fatni Mufit; Fuja Novitra (Postgraduate, University of Mataram, 2026)
This needs assessment study reveals a significant gap between the demands of the Merdeka Curriculum and the actual conditions of disaster-related learning about volcanoes in schools located in high-risk eruption areas of West Sumatra. Although the learning outcomes require students to design simple mitigation strategies, most schools have not achieved these competencies due to students’ low understanding of evacuation procedures and disaster preparedness. This situation is exacerbated by limited infrastructure: the majority of schools lack functional science laboratories and have very restricted internet access. However, there is strong potential shown by students' high enthusiasm for creative project-based learning. Therefore, the development of low-cost, low-tech, fully offline interactive project media using local or recycled materials is urgently needed. Such media are expected to improve students' scientific understanding of volcanic hazards, enhance disaster literacy, and foster creativity, critical thinking, and the competencies mandated in the Pancasila Student Profile. Thus, this media development serves as a strategic solution to support sustainable education in disaster-prone regions.